Penerapan Metode Scrum untuk Sistem Informasi Arsip Surat di Kantor Kecamatan Umbu Ratu Nggay Barat - Serlince Nono; Adelbertus Umbu Janga; Lidia Lali Momo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The implementation of an effective and efficient information system is very important in managing letter archives in government offices. This study aims to design and implement a letter archive information system using the Scrum method at the Umbu Ratu Nggay Barat District Office. Scrum was chosen as a software development framework because of its adaptive and iterative nature, allowing the team to accommodate changing needs quickly. Through this approach, system development is carried out in several sprints, which ensures that the development process runs in a structured manner with a clear division of tasks. The results of this study indicate that the implementation of the Scrum method can increase efficiency in the letter archive management process and accelerate the response to changes in system needs. With this letter archive information system, the sub-district office can manage letter documents in a more organized, easily accessible, and secure manner. This study is expected to be the basis for further development to improve the quality of administrative services in government institutions.